Medical laboratory wastewater treatment by electro-fenton process: Modeling and optimization using central composite design - Basturk, Irfan; Varank, Gamze; Murat Hocaoglu, Selda; Yazici Guvenc, Senem (WILEY, 2021)
Medical laboratory wastewaters arising from diagnosis and examination units show highly toxic characteristic. Within the scope of the study, removal of the wastewater's toxicity and increasing BOD5/COD ratio of the medical laboratory wastewaters through electro-Fenton (EF) process were investigated. In the study, central composite design was applied to optimize the process parameters of EF for COD, BOD5, and toxicity unit (TU) removal. Based on ANOVA, H2O2/COD was found to be significant parameter for COD removal, whereas current, reaction time, and H2O2/COD were determined to be significant parameters for BOD(5)and TU removal. Optimum conditions (pH value of 3.4, current 3 A, reaction time 33.9 min, and H2O2/COD of 1.29) were determined, and predicted removals of COD, BOD(5,)and TU were found to be 55.1%, 42.5%, and 99.7% and experimental removals were found to be 53.4%, 41.2%, and 99.5%, respectively. TU value of the wastewater decreased from the value of 163-0.815, and BOD5/COD value increased from the value of 0.32-0.39. The results of the study indicate that EF process is an effective treatment option for COD, BOD(5,)and especially toxicity removal from medical laboratory wastewater. Practitioner points Electro-Fenton process was applied medical laboratory wastewater with highly toxic characteristic. Response surface methodology approach using central composite design was employed for modeling. 53.4%, 41.2%, and 99.5% of COD, BOD(5,)and toxicity removals were achieved under statistically optimized conditions. TU value of the wastewater decreased from the value of 163-0.815. BOD5/COD value increased from the value of 0.32-0.39.
Keywords: modeling; optimization; toxicology; wastewater treatment; RESPONSE-SURFACE METHODOLOGY; ADVANCED OXIDATION PROCESSES; AQUEOUS-SOLUTIONS; REMOVAL; DEGRADATION; EFFICIENCY; ALUMINUM; PRETREATMENT; DESTRUCTION; WASTEWATERS; Engineering; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources